Protein supplements - the right whey. - Peh, Lee Ling. (2013)
The Right Whey Campaign is a Nanyang Technological University student-run initiative for their Final Year Project. It aims to educate youths in Singapore to consume protein and protein supplements safely and responsibly. This campaign report documents the team’s campaign journey from pre-campaign planning to execution and the post-campaign evaluation. Targeting active tertiary students, the campaign has two main aspects its execution – online presence and offline activation. The main drivers for the campaign’s online presence are the website and Facebook page. Online engagement activities such as contests and accessible content have built an audience-base that was tapped into for the offline activation, which comprises of roadshows and talks at different tertiary institutions. Activities held during the roadshows were integrated with online drivers to ensure that conversion of target audience to active participants is sustained throughout the entire campaign. Although the campaign has achieved its objectives in its evaluation, the limitations met and approaches for improvement were discussed for future considerations to continue with the campaign.